2021
DOI: 10.1186/s12985-021-01627-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on the prevalence of respiratory viruses in children with lower respiratory tract infections in China

Abstract: Background The multifaceted non-pharmaceutical interventions (NPIs) taken during the COVID-19 pandemic not only decrease the spreading of the SARS-CoV-2, but have impact on the prevalence of other viruses. This study aimed to explore the prevalence of common respiratory viruses among hospitalized children with lower respiratory tract infections (LRTI) in China during the COVID-19 pandemic. Methods Respiratory specimens were obtained from children w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
107
2
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 24 publications
19
107
2
6
Order By: Relevance
“…This finding is similar to an earlier study in 2009-2014 in Southern China where influenza, RSV and ADV were found to be the most common respiratory viruses (Zhang et al, 2014;Liao et al, 2015). Most of our samples were collected from outpatients and hence better reflected respiratory virus activity in the community, when compared to studies which focused on hospitalized patients and may be affected by revised admission criteria as part of the pandemic response (Fukuda et al, 2021;Liu et al, 2021). In early 2020 when the most stringent control measures against COVID-19 were implemented, influenza viruses among children and adults were suppressed to a historically low level in Guangzhou as well as in many parts of the world (Olsen et al, 2020;Zipfel et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…This finding is similar to an earlier study in 2009-2014 in Southern China where influenza, RSV and ADV were found to be the most common respiratory viruses (Zhang et al, 2014;Liao et al, 2015). Most of our samples were collected from outpatients and hence better reflected respiratory virus activity in the community, when compared to studies which focused on hospitalized patients and may be affected by revised admission criteria as part of the pandemic response (Fukuda et al, 2021;Liu et al, 2021). In early 2020 when the most stringent control measures against COVID-19 were implemented, influenza viruses among children and adults were suppressed to a historically low level in Guangzhou as well as in many parts of the world (Olsen et al, 2020;Zipfel et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the use of an epidemiologic integrated approach has to be highlighted whereas the widest use of non-pharmaceutical interventions (NPIs) during the current COVID-19 pandemic has changed the epidemiologic scenario of influenza and other respiratory viruses [58,59], with a decline of influenza and hRSV detection followed by a resurgence of hRSV incidence in hospitalised children after the relaxation of public health measures [60,61]. Therefore, the importance of molecular epidemiology, in support of the surveillance systems in place against respiratory pathogens both in community and hospital settings, must be emphasised also in the light of a changing and more complex global public health scenario and of the increasing need to update vaccination strategies [62,63].…”
Section: Discussionmentioning
confidence: 99%
“… 15 However, recent evidence suggests that some other respiratory viruses showed a propensity to reemerge. 16 Although some studies have reported the impact of the pandemic on the prevalence of respiratory viruses in children, 17 , 18 , 19 , 20 few studies have focused on the influence of the NPIs on the circulation of common respiratory viruses in children of different age groups. Therefore, our study was conducted to report, and discuss the change in the epidemiological characteristics of common respiratory viruses in children of different ages under the COVID‐19 pandemic and provide support for finding better protection strategies.…”
Section: Introductionmentioning
confidence: 99%